2018
DOI: 10.1080/00380768.2018.1493341
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential for top-dressing bread wheat with ammonium chloride to minimize grain yield losses under drought

Abstract: The frequency and severity of drought is predicted to rise in many parts of the world. Considering that drought is the main constraint on rain-fed wheat crop production, both agronomic and genetic measures have been taken to minimize yield losses under drought. Beyond its role as a micronutrient, chloride also acts as an osmoticum, implicated in the regulation of stomatal aperture. This study explores the potential for chloride fertilization of Australian bread wheat (Triticum aestivum L.) to minimize grain yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Our data thus indicate that the two analysed wheat genotypes prioritize different N compounds for transport and grain loading. Previous studies in Mace suggest that this cultivar has high N use efficiency (Mahjourimajd et al 2016) and this study and Kastury et al (2018) additionally demonstrated that Mace is higher yielding under drought than RAC875. The possibility that the superior performance of Mace may be related to the preferential use of metabolites with high N:C ratio, which are more energy effective forms for transporting and storing N, is an intriguing hypothesis that requires further validation.…”
Section: Allantoin Is a Relevant Component Of Grain Nitrogen In Wheatsupporting
confidence: 73%
“…Our data thus indicate that the two analysed wheat genotypes prioritize different N compounds for transport and grain loading. Previous studies in Mace suggest that this cultivar has high N use efficiency (Mahjourimajd et al 2016) and this study and Kastury et al (2018) additionally demonstrated that Mace is higher yielding under drought than RAC875. The possibility that the superior performance of Mace may be related to the preferential use of metabolites with high N:C ratio, which are more energy effective forms for transporting and storing N, is an intriguing hypothesis that requires further validation.…”
Section: Allantoin Is a Relevant Component Of Grain Nitrogen In Wheatsupporting
confidence: 73%
“…Kukri is derived from CIMMYT wheat lines and was adapted at the University of Adelaide Roseworthy breeding programme for 1999 release by Seednet. Gladius is derived from a complex cross and was selected by breeders for grain yield maintenance under drought stress, and then publicly released in 2007 (Kastury et al 2018;Melino et al 2015). Gladius was documented as high yielding under drought conditions (Bennett et al 2012;Izanloo et al 2008), and both Gladius and Kukri have previously demonstrated high N use efficiency (Mahjourimajd et al 2016;Sitlington Hansen 2019).…”
Section: Glasshouse Plant Experiments Set-upmentioning
confidence: 99%
“…Nitrogen top-dresses application after tillering is needed by most crops. In agricultural soils nitrate concentrations are generally 10 times higher than ammonium [6], so in some studies like [7,8] use of top-dressing with ammonium leads to increase in growth, grain yield, photosynthetic rate in cereals. If it is used before GS30 (Start of stem elongation), it can increase tiller numbers and dry matter, leading to yield increases; but nitrogen top-dress after GS30 can improve tiller survival and so maintain yields because of rapid N uptake and increases in canopy size through leaf emergence.…”
Section: Introductionmentioning
confidence: 99%